PESAN AL QUR'AN TENTANG PENDIDIKAN - Syaifurrohman, Amir; Lestari, Fina Ailika; Nurrohmah, Nisa (Jurnal Pendidikan Teknologi Informasi (J-Diteksi), 2025)
The Qur'an, as a book of revelation that is a guide to life for Muslims, contains various messages and teachings that are relevant to various aspects of life, including education. Education from the perspective of the Qur'an is not only limited to the transfer of knowledge, but also includes the formation of character and morals. Education from the perspective of the Qur'an covers various aspects, including science, morals and spirituality. The Qur'an always encourages its readers to always seek knowledge and improve their abilities, this is reflected in the first revelation regarding the command "iqra" (read). The Qur'an's message about education includes not only academic knowledge, but also holistic self-development, which includes intellectual, emotional and spiritual dimensions. Therefore, the Qur'an provides a solid foundation for an education system that can form individuals who are not only intelligent, but also have noble character and social awareness. The Al-Qur'an teaches several messages that can be applied in the world of education. Among the educational messages mentioned in the Al-Qur'an and which are the focus in this article include; Tarbiyah, Iqra', Ta'lim, Mauidhah Hasanah, Tausiyyah, Al-Uswantun Hasanah.